The influence of Organizational Support and Management of Employee Performance Marketing in Mediation by Competence - -, Magus Sitindaon; Hery Winoto Tj; Melitina Tecoalu (International Journal of Science, Technology & Management, 2021)
These studies identify and analyze the implications of organizational support, management support, and employee competence on employee performance marketing. The study population was all employees of the marketing BPR Nusantara Bona Pasogit Group Region of West Java and Banten, which amounted to 115 people. Probability sampling technique is made to sampling, a total of 115 respondents who are employees of the marketing BPR Nusantara Bona Pasogit Group Region of West Java and Banten became the sample in the study. This study uses the approach of analysis of structural equation (SEM) using smartPLS. The results of the analysis indicates organizational support has an influence on employee performance marketing at BPR Nusantara Bona Pasogit (NBP) Group Region of West Java and Banten, as well as management support affect the performance of employees marketing at BPR Nusantara Bona Pasogit (NBP) Group Region of West Java and Banten.Disampingitu found also that the support of the organization affect the competence of employees of marketing at BPR Nusantara Bona Pasogit (NBP) Group Region of West Java and Banten.